Triamcinolone acetonide injection in the treatment of upper eyelid retraction in Graves' ophthalmopathy evaluated by 3.0 Tesla magnetic resonance imaging - Miao Duan; Dong-Dong Xu; Hai-Long Zhou; Hong-Ying Fang; Wei Meng; Yi-Ning Wang; Zheng-Yu Jin; Yu Chen; Zhu-Hua Zhang (Indian Journal of Ophthalmology, 2022)
Purpose: To evaluate changes in the levator palpebrae superioris (LPS) muscle on 3.0 T magnetic resonance imaging (MRI) after triamcinolone acetonide injection for treating upper lid retraction (ULR) with Graves' ophthalmopathy (GO) and to explore the value of LPS muscle quantitative measurement for clinical treatment. Methods: Patients with GO showing ULR were studied retrospectively and they underwent 3.0 T MRI scans before and after subconjunctival injection o f triamcinolone acetonide. The largest thickness (T) and highest signal intensity (SI) of LPS muscle on the affected eyes were measured in the sequences of coronal T2-weighted, fat-suppressed fast spin echo imaging (T2WI-fs) and T1-weighted, fat-suppressed, contrast-enhanced fast spin echo imaging (T1WI-fs + C), respectively. The SI ratio (SIR) (LPS muscle SI/ipsilateral temporalis SI) was calculated individually. Depending on the therapeutic effect, patients were divided into effective group and non-effective group. Independent t-test was used to compare SIR and T of LPS muscle in different treatment groups before treatment, and paired sample t-test was used to compare SIR and T of LPS muscle before and after treatment. Then cut-off level for predicting therapeutic effect and the receiver operating characteristic curve (ROC) curve were analyzed. Results: Sixty-two patients (77 eyes) were enrolled. After treatment, the T of LPS muscle showed significant decrease in all sequences in both effective and non-effective treatment groups. However, changes in SIR of LPS muscle in the two groups were different; SIR of LPS muscle on T2WI-fs and T1WI-fs + C decreased after treatment in the effective group (PT2 < 0.001, PT1 + C < 0.001) and SIR of LPS muscle showed no statistically difference in all sequences (all P > 0.05) in the non-effective group. There was a correlation between SIR of LPS muscle before treatment and after treatment with triamcinolone acetonide injection, which was that SIR of LPS muscle in the effective treatment group was lower than that in the non-effective treatment group on T1WI-fs + C (P < 0.001). SIR of LPS muscle on T1WI-fs + C showed 87.5% sensitivity and 66.7% specificity to predict therapeutic effect (area under the ROC curve [AUC] = 0.840). Conclusion: In GO patients with ULR, 3.0 T MRI can be used to evaluate the response of triamcinolone acetonide injection. SIR of LPS may be a predictor of its efficacy.